Surface treatment in bonding technology - Rudawska, Anna (Academic Press, an imprint of Elsevier, 2019)
Surface Treatment in Bonding Technology provides valuable advice on surface treatment methods, modern measuring devices, and the appropriate experimentation techniques that are essential to create strong joints with a reliable service life. The book's focus is on the detailed and up-to-date analysis of surface treatment methods for metallic and polymer substrates. An analysis of factors affecting the surface preparation stage, together with advice on selection, is also provided. Essential theory is combined with experimentation techniques and industry practice to provide a guide that is both practical and academically rigorous. Including a general introduction to bonding, as well as coverage of mechanical, chemical and electrochemical methods, this book is the ideal primer for anyone working with or researching adhesive bonding.